2018
DOI: 10.31989/ffhd.v8i6.407
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity and haematological effects of Malaysia Hibiscus sabdariffa L. aqueous extract on obese Sprague Dawley rats

Abstract: Background: Hibiscus sabdariffa L. (Hs; Malvaceae) is commonly known as roselle or red sorrel in English or karkadè in Arabic. It is a tropical plant native to India and Malaysia. Roselle extracts have been widely reported to have beneficial health effects. The aim of this study was to determine the effective dose of Hs aqueous extract, which is a possible reducing agent in diet-induced obese rats, and monitoring any toxicological effect.Methods: Male Sprague Dawley rats (n= 24) aged 6-7 weeks and weighing 210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
0
12
0
7
Order By: Relevance
“…Both cold and hot beverages of Roselle red calyces (CRB and HRB, respectively), as noticed in Table 3, induced significant decreases compared with untreated lead-exposed group, however, CRB was so efficient that could return BWG toward its normal value. The weight loss promoting effect of Hibiscus sabdariffa L. calyx beverages (CRB and HRB) is in harmony with Omar et al (2018) who revealed that oral SAMAH A. EL-HASHASH administration of Hs aqueous extracts (150,200,250, and 300 mg/kg) for 10 weeks caused a dosedependent reduction in BWG and abdominal fat in obese rats. The mechanisms by which Hs can induce weight loss were investigated in many studies.…”
Section: Body Weight Gain and Absolute And Relative Liver And Spleen Weightsmentioning
confidence: 52%
See 2 more Smart Citations
“…Both cold and hot beverages of Roselle red calyces (CRB and HRB, respectively), as noticed in Table 3, induced significant decreases compared with untreated lead-exposed group, however, CRB was so efficient that could return BWG toward its normal value. The weight loss promoting effect of Hibiscus sabdariffa L. calyx beverages (CRB and HRB) is in harmony with Omar et al (2018) who revealed that oral SAMAH A. EL-HASHASH administration of Hs aqueous extracts (150,200,250, and 300 mg/kg) for 10 weeks caused a dosedependent reduction in BWG and abdominal fat in obese rats. The mechanisms by which Hs can induce weight loss were investigated in many studies.…”
Section: Body Weight Gain and Absolute And Relative Liver And Spleen Weightsmentioning
confidence: 52%
“…The mechanisms by which Hs can induce weight loss were investigated in many studies. They included the ability of Hs to suppress appetite and adipogenesis and inhibit the activities of carbohydrate digestive enzymes including α-/β-glucosidase and α-amylase (Omar et al, 2018;Ojulari et al, 2019;Gondokesumo et al, 2017).…”
Section: Body Weight Gain and Absolute And Relative Liver And Spleen Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the weight loss-promoting impact of Hibiscus sabdariffa L. calyx beverages (CRB and HRB) was reported from many previous studies. In this regard, it was revealed that oral Hs aqueous extract administration (150, 200, 250, and 300 mg/kg) for 10 weeks caused a dose-dependent reduction in BWG and abdominal fats in obese rats [ 32 ]. The mechanisms by which Hs can induce weight loss were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…H. sabdariffa Linn. has been known as anti‐obesity because it has prevented or reduced bodyweight in obese rats (Anna Sheba & Ilakkia, 2016 ; J. K. Kim et al., 2007 ; Omar et al., 2018 ). The polyphenols in HSE prevent weight gain in diet‐induced‐obesity (Guardiola and Mach) rats and inhibit lipogenesis in the white adipose tissue at the molecular level (Herranz‐Lopez et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%